NEW INSTRUMENTS OF LITERARY RESEARCH: INTERDISCIPLINARY CHALLENGES - Žakevičienė, Indrė (Via Latgalica, 2013)
The aim of the article is to reveal the new possibilities of interdisciplinary studies and to ponder upon possible contribution of the researchers of the humanities into the work of environmentalists and ecologists while seeking effective solutions, concerning the whole biosphere and ecosystem, to discuss the possibilities of cooperation of the researchers of different fi elds of interest (linguists, psychologists, philosophers) while analysing literary texts, to emphasise the role of literature trying to revive the so- called ecological sub-consciousness of an individual, and changing one’s attitude towards the environment, to introduce the Reception Theory and the Cognitive Poetics as specifi c literary tools, basic to modern literary analysis because of their emphasis on readers’ reactions and their particular cognitive processes, experiencing literary texts.